Environmental Cost Disclosure and Financial Performance of Oil and Gas Firms: Pengungkapan Biaya Lingkungan dan Kinerja Keuangan Perusahaan Minyak dan Gas Bumi - Sunday, Fred Itotaziba; Chimezie, Nwosu Eleazar (Indonesian Journal of Law and Economics Review, 2024)
General Background: The relationship between environmental cost disclosure and financial performance is essential in environmentally impactful sectors like oil and gas. Specific Background: This study focuses on listed oil and gas firms in Nigeria, examining health and safety costs and waste management costs as predictors of return on assets (ROA). Knowledge Gap: Existing research shows inconsistent findings on the effects of environmental disclosures on financial performance, necessitating further investigation. Aims: This study aims to clarify the impact of environmental cost disclosures on financial performance, particularly through health and safety and waste management costs. Results: Using ex-post-facto research design and secondary data analysis, the findings reveal a significant positive relationship between environmental cost disclosures and financial performance, highlighting the importance of these costs on ROA. Novelty: By applying legitimacy theory and focusing on specific environmental costs, this research fills a gap in Nigerian literature. Implications: The study recommends enhanced environmental policies for oil and gas firms, promoting accountability and aligning financial performance with ecological responsibilities. Highlights: Significant positive relationship exists between environmental cost disclosures and financial performance (ROA) in Nigerian oil and gas firms. Health and safety costs and waste management costs are critical predictors of financial performance. The study emphasizes the need for enhanced environmental policies and corporate accountability in the oil and gas sector. Keywords: Health, Safety Cost, Waste Management Cost, ROA